(untitled) (Journal of Scientific Research, 2013)
Triglycine sulphate (TGS), an important ferroelectric material has been widely used in the fabrication of high sensitivity infrared detectors at room temperature. Single crystals of KDP doped TGS was grown by slow evaporation method at room temperature in this study. The grown crystal was characterized by UV-Vis spectroscopy, FTIR spectroscopy, powder X-ray diffraction studies, and ferroelectric studies. KDP doped TGS crystals were found to be highly transparent and full faced. The experimental results evidence the suitability of the grown crystal for optoelectronic applications. Keywords: Crystal growth; KDP-doped TGS; Ferroelectric studies © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.16584 J. Sci. Res. 6 (1), 1-9 (2014)